Optimasi Waktu dan Biaya dengan Metode Crashing pada Proyek Pembangunan Jalan Simp. 4 Kaliorang – Talisayan Kalimantan Timur - Nardiansyah, Afrie; Intansari, Dyah Widi Astin (Jurnal Kridatama Sains dan Teknologi, 2022)
A common construction problem is delays in project implementation. Delays on the project will affect the cost of the project. Seeing this incident, this study will analyze the acceleration of project time on the Road Construction project Simp. 4 Kaliorang - Kalisayan using the Precedence Diagram Method (PDM) using Microsoft Project 2010 software, so that jobs are on the critical path. The work that is on the critical path will be crashing with the method of adding working hours (overtime), and adding tools, the final result of the two alternative crashing will be a change in the acceleration of the duration of a project at an optimal cost. From the results of time and cost optimization research with the crashing method on the road construction project simp. 4 kaliorang - talisayan using the alternative of additional working hours (overtime) for 3 hours, 4 hours, 5 hours, and 6 hours and the second alternative with variations in the addition of tools and energy by 25%, 50%, 75% and 100% of the total equipment and normal power obtained the final result of the most optimum alternative of the two alternatives is the alternative of adding tools and energy by 100% of the number of normal tools and energy, the crash duration is 91 days from the normal duration of 135 days or an acceleration of duration of 44 days, with a total cost of Rp. 10,825,046,816.96 from the normal total cost of Rp. 10,868,916,625,88 or a decrease in total costs of 0.40%. Keywords: Delays, critical path, crashing, additional working hours (overtime), additional workforce, PDM (Precedence Diagram Method)